Forecasting Supply of Commerical Office Buildings Using Polynomial Distributed Lag Model - Sing, Michael; Love, Peter; Wang, Xiangyu; Smith, J. (RICS 2012, 2012)
Forecasting the supply of commercial office buildings is critical for the economic development. Using the data from Hong Kong, the major factors influencing the supply of commercial office buildings such as gross domestic product, property prices, vacancy rates, interest rate are examined. Unlike the investment in financial assets, commercial office building developments are characterized by a time lag from the decision to build until their completion. The lead-lag structure of these major factors in determining the supply of office buildings is identified. Using the technique of polynomial distributed lag, the lead-lag model is simulated, and provides a reliable forecast on the supply of office buildings. Considering the prevailing shortage of commercial office buildings as result of economic growth in Asia, the forecasts derived from the model are deemed to be useful for economists and property analysts to facilitate their investment decision-making in the future.